Ada Apa Dengan Gereja Ayam? Tipologi dan Motivasi Wisatawan Terstimulasi Film di Rumah Doa Bukit Rhema - Zhaki Anggadewi Hemaradevi (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2020)
Typology and motivation of tourists is a research topic that continues to be discussed in tourism research. This is because every tourist as an individual is a unique creature and no two individuals are alike. Based on the characteristics of typology and knowing motivation can help the stakeholders to better understand the needs of tourists so that destination can reach the satisfaction of visitors. This research is a quantitative descriptive research that aims to determine the typology and motivation of tourists at Rumah Doa Bukit Rhema. Rumah Doa Bukit Rhema or better known as Gereja Ayam is one of the destinations that appear in the movie Ada Apa Dengan Cinta 2. Rumah Doa Bukit Rhema which was originally built for the purpose of prayer house for all religious people became famous among domestic tourists after appearing in the film, because of the uniqueness of this destination as a religious place as well as tourist destination.The method used in this research is a survey with purposive sampling technique. The result of this research showed that based on Macionis (2004) typology, the general film tourists has the greatest number compared to other typology. The motivation that encourages respondents to visit is the novelty, novelty can be interpreted as a desire to see something new or something that can’t be encountered in everyday life.